Sistem Penunjang Keputusan Kelayakan Kenaikan Gaji Karyawan Maestro Parfum Yogyakarta - siadari, salomo halomoan (JATISI, 2024)
The performance appraisal for salary increases at Toko Maestro Parfum is still done manually, leading to employee dissatisfaction due to lack of objectivity and fairness in the evaluation process. Simple Additive Weighting (SAW) is a suitable approach for this purpose, as it identifies the optimal option among several choices based on assigned weights from the performance assessments of each option. This method is chosen for its ability to select the best option according to predefined criteria. Black Box testing of this system indicates its alignment with the requirements for evaluating employee performance. Test results indicate that 6 out of 10 employees, or 60%, are eligible for a salary increase. Therefore, the implementation of this system is expected to effectively and efficiently improve the salary appraisal process at Toko Maestro Parfum.